DETERMINATION OF THE LEVEL OF OVERVOLTAGE IN THE SECONDARY CIRCUITS OF SUBSTATIONS WHEN LIGHTNING IMPULSE VOLTAGE IS DISTRIBUTED IN HIGH-VOLTAGE BUSES - V. I. Glushko; E. A. Deryugina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
Lightning voltage impulse due to the waves of storm surge rolling out the high voltage line to a substation causes current to flow in the buses that, due to magnetic effect, induces overvoltage in the secondary circuit. Overvoltage in the system “wire – ground” is considered as obstructions which are hazard in relation to the possibility of electrical damage of the devices of relay protection and automation of substations. With the use of the inverse Laplace transformation, the solution of the problem the magnetic influence of the primary circuits to secondary circuits in the time domain depending on time of transition, which always occurs during the distribution of the voltage impulse in the buses, has been obtained. Estimation of the level of overvol tage in the system “wire – ground” for the case of failure of a bus nonlinear surges and arresters when lightning impulse of voltage is distributed on the buses along their length without deformation has been fulfilled. Solutions are obtained for overvoltage in the secondary circuits, according to which the levels of overvoltage can be estimated as “extremely stepped-up”, “lowered” and “averagely stepped-up” levels. With a method of computational experiment the levels of overvol tage for distribution substations with voltage 110 and 220 kV were assessed. The results are compared with the normalized values of the interference voltage. The suggested method of calculation of impulse magnetic influence of the primary circuits on the secondary circuits of substations while lightning impulse voltage is being distributed in high voltage buses for the case of failure of a nonlinear surge and arresters at the stage of design and operation of substations can be used as a test method for estimation of electrical durability of relay protection and automatic equipment from lightning and switching overvoltage.